The immunoadjuvant effect of soluble glucan derivatives in mice - Wagnerová, J; Lísková, A; Cervenáková, L; Trnovec, T; Ferencík, M (Folia microbiologica, 1991)
We examined the effect of soluble derivatives of yeast glucan on the humoral immune response of various strains of inbred mice after administration of different doses according to various schedules. Glucan was injected i.v. or s.c. in a single dose or repeatedly. The immune response was examined by determining the titres of serum hemagglutinins against sheep erythrocytes (SRBC-Ab). The immunoadjuvant effect of glucan derivatives depends on the inbred strain used, on the dose of glucan, mode and time of administration with respect to antigen injection. The results have shown that the stimulatory effect of glucan derivatives occurred already after a single injection, the optimum dose being 10-20 mg/kg. Intravenous injection was more efficient than the subcutaneous one. In some cases, a slight increase of the spleen mass was observed.
Keywords: Yeasts; Sheep; Antibody Formation; druhová specificita; Adjuvants, Immunologic; adjuvancia imunologická; Dose-Response Relationship, Immunologic; Female; hemaglutininy; zvířata; Hemagglutinins; myši; myši inbrední C57BL; kvasinky; Glucans; Mice; Mice, Inbred CBA; Mice, Inbred A; ženské pohlaví; tvorba protilátek; Mice, Inbred C57BL; Species Specificity; glukany; Animals; myši inbrední CBA; imunologická odpověď na dávku; myši inbrední A; ovce